Securing electronic transactions via payment gateways: a systematic review - Olanrewaju, Rashidah Funke; Khan, Burhan Ul Islam; Mattoo, M. Mueen Ul Islam; Anwar, Farhat; Nordin, Anis Nurashikin; Mir, Roohie Naaz (Inderscience, 2017)
This study focuses on the means to ensure the security and success of electronic payments which form part and parcel of e-commerce. This paper also highlights the primary functions, purpose, and benefits attached with payment gateways besides discussing the essential pre-requisites for payment gateways to be qualified as strong payment gateways. This is necessary to securely process, authorise and route local and international monetary exchanges carried out by clients utilising different alternative delivery channels (ADCs). In this paper, payment gateways most popularly used have been studied, and their comparison has been performed on criteria such as security, cost, customer support, etc. Based on the gathered information, the security concerns related to payment gateways have been taken up that need to be mitigated. Several recommendations have been presented after analysing the security limitations in payment gateway structure for the customers before accepting and while using such a means of payment for their transactions online.